2018
DOI: 10.3390/biom8030086
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Associations between Homoarginine, Intermediate Phenotypes, and Atrial Fibrillation in the Community—The Gutenberg Health Study

Abstract: Homoarginine has come into the focus of interest as a biomarker for cardiovascular disease. Atrial fibrillation (AF) causes a substantial increase in morbidity and mortality. Whether circulating homoarginine is associated with occurrence or persistence of AF and may serve as a new predictive biomarker remains unknown. We measured plasma levels of homoarginine in the population-based Gutenberg health study (3761 patients included, of them 51.7% males), mean age 55.6 ± 10.9 years-old. Associations between homoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Previously, we found that patients with persistent atrial fibrillation at the time of blood sampling had the lowest homoarginine concentrations compared to paroxysmal atrial fibrillation [22]. In contrast, homoarginine levels did not correlate with the occurrence or persistence of atrial fibrillation in a population-based study [32]. Therefore, it seems likely that the association of homoarginine with atrial fibrillation depends on the underlying pathology.…”
Section: Discussionmentioning
confidence: 81%
“…Previously, we found that patients with persistent atrial fibrillation at the time of blood sampling had the lowest homoarginine concentrations compared to paroxysmal atrial fibrillation [22]. In contrast, homoarginine levels did not correlate with the occurrence or persistence of atrial fibrillation in a population-based study [32]. Therefore, it seems likely that the association of homoarginine with atrial fibrillation depends on the underlying pathology.…”
Section: Discussionmentioning
confidence: 81%
“…However, in the community-based cohort of the Framingham Heart Study, ADMA and SDMA were not independently associated with the incidence of AF [23]. In the general population of the Gutenberg Health Study higher ADMA was associated with prevalent AF, whereas no association was seen for SDMA or hArg [24,25]. In CAD patients, lower hArg was associated with a higher prevalence of AF and an increased risk for incident fatal and non-fatal stroke or MI and all-cause mortality [26].…”
Section: Discussionmentioning
confidence: 99%
“…The biomarker and causal roles of hArg in the development of cardiometabolic diseases [42], and cross-sectional associations between hArg, intermediate phenotypes and atrial fibrillation in healthy humans [43] were recently investigated. The relationship between hArg and the methionine-homocysteine balance was investigated in patients with ischemic heart disease [44].…”
Section: Andandmentioning
confidence: 99%